(untitled) (Scottish Historical and Archaeological Internet Reports, 2013)
The following paper presents the results of two excavations undertaken in 1999 and 2000 within parts of the World Heritage Site of the Old Town of Edinburgh and the Canongate (NGR: NT 2665 7377). Excavation at Plot N of the Holyrood North Re-Development Project, Holyrood Road, unearthed evidence of medieval boundary works (including a possible 12th-century burgh ditch), a 17th-century well, a medieval graindrying kiln, refuse pits, drainage features and post-medieval cultivation soils. Excavation alongside Calton Road revealed evidence of medieval/post-medieval property divisions, cultivation soils and quarry pits. Both sites yielded significant artefact assemblages.